Toward sustainable food systems: Circular economy practices and perspectives of small-scale producers in the Bega Valley - Catherine Lucas; Anita Stefoska-Needham; Spring Zhou; Namal Bandaranayake; Senevi Kiridena; Chris Brennan-Horley; Suzanne Pickles; Nicole Cook; Sam Quirk; Karen Charlton (Journal of Cleaner Production, 2026)

Environmental Drivers of Recruitment Variability in Narrow‐Barred Spanish Mackerel Scomberomorus commerson Lacépède, 1800 - Susannah M. Leahy; Joanne Langstreth; Rik C. Buckworth; Peri Subritzky; Olivia J. Whybird; Sam M. Williams; Lucas I. Sumpter; Jonathan D. Mitchell (Fisheries Oceanography, 2026)
Understanding the effects of environmental conditions on fisheries resources is crucial for guiding the effective assessment and management of fish stocks. Previously assessed as depleted, the narrow‐barred Spanish mackerel fishery on the east coast of Queensland, Australia, is under management intervention to rebuild the stock. In this study, we use long‐term age composition data to reconstruct 24 years of historic year class strength and explore a broad range of potential environmental influences on recruitment variability in the fishery. Year class strength was extremely well captured (76%–84% deviance explained) by generalised additive models containing just four environmental indices. Recurring key environmental indices in top models included environmental conditions prior to spawning (large scouring flood events during the wet season before spawning and cool winter sea surface temperature immediately prior to spawning), during spawning (unseasonal flooding near the spawning grounds), during larval dispersal and proxies for food availability for juvenile Spanish mackerel. These results have since been used to hindcast recruitment variability in the fishery prior to the collection of the age‐composition data to better understand historic fluctuations in the fishery, and can also be incorporated into management strategies for rebuilding the stock.

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Population Genomics of a Cosmopolitan Weed Provides Insights Into Its Local Adaptation and Recent Demographic History - Marilia Souza Lucas; Christoph Rosche; Isabell Hensen; Stefan G. Michalski; Dávid U. Nagy; Diana Gamba; Renske E. Onstein; Karime Abidkulova; Mohammad Al‐Gharaibeh; Ali A. Al‐Namazi; Sirwan Babaei; Fernando Bastida; et al. (Molecular Ecology, 2026)
Invasive plant species present a growing ecological and economic challenge, and often adapt rapidly to their novel environments through complex demographic and evolutionary processes. Invasion genomics offers powerful tools to disentangle these processes, but most studies rely on geographically narrow sampling across native and non‐native ranges. Erigeron canadensis is a cosmopolitan weed native to North America that has successfully invaded diverse climates worldwide. We used double‐digest restriction site‐associated DNA sequencing (ddRADseq) to investigate the genetic diversity and structure of 280 E. canadensis populations across the Northern Hemisphere. We found that native and non‐native populations maintained comparable genetic diversity. Population structure analyses revealed four genetic clusters that were mainly differentiated along latitudinal and aridity gradients. However, one cluster was strongly overrepresented in the non‐native compared to the native range. In the native range, genetic differentiation was shaped by spatial and environmental gradients, while in non‐native regions human‐mediated dispersal and repeated introductions disrupted environmentally driven genetic structure. Migration network analyses revealed limited intercontinental connectivity and a possible role of long‐distance dispersal in within‐range expansions. Genomic offset analyses showed that genotype‐environment mismatches in non‐native populations associated with reduced growth and reproduction. Together, our results indicate that the invasion dynamics of E. canadensis were driven by multiple introductions, population admixture, and lineage sorting, while some genotypes contributed disproportionately to the spread of this invader. The presence of apparent maladaptation suggests that even long‐established invaders may still be evolving in response to their novel environment, raising concerns about potential future expansions.

Preoperative coronary evaluation in valve surgery for infective endocarditis: findings from a multicenter retrospective study - Lucas Armange; Pauline Blanc Petitjean; Audrey Le Bot; David Luque Paz; Raphaël Lecomte; Sylvain Jaffuel; Pierre-Guillaume Piriou; Vincent Letocart; Romain Didier; Sam Sharobeem; Marc Bedossa; Erwan Flecher; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Effects of a mixture of mulching film microplastics on soil properties, microbial activities, and plants in terrestrial mesocosms with and without earthworms - Klára Šmídová; Sam van Loon; Laura J. Zantis; Sylwia Adamczyk; Lotte de Jeu; Rachel Hurley; Sarmite Kernchen; Chiara Consolaro; Bartosz Adamczyk; Luca Nizzetto; Thijs Bosker; Salla Selonen; et al. (Journal of Hazardous Materials, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Microplastics from biodegradable mulching films affect soil physicochemical properties and earthworm reproduction, but not microarthropod communities - Sam van Loon; Lotte de Jeu; Shin Woong Kim; Rachel Hurley; Laura J. Zantis; Salla Selonen; Luca Nizzetto; Tessa Steenhof; Chiara Consolaro; Matty P. Berg; Cornelis A.M. van Gestel (Applied Soil Ecology, 2026)

Sublethal effects of microplastics sourced from polypropylene agricultural plastics on four soil invertebrate species - Sam van Loon; Vili Saartama; Klára Šmídová; Anita Jemec Kokalj; Primož Zidar; Giuseppe P. Salanitri; Paolo Riccobene; Luca Gargiulo; Jakub Hofman; Rachel Hurley; Luca Nizzetto; Jari Haimi; et al. (Journal of Hazardous Materials, 2025)

Toxicity of two different size classes of tire particles from mixed end-of-life car tires to the springtail Sinella curviseta - Lucas M. Hulscher; Sam van Loon; Cornelis A.M. van Gestel (Chemosphere, 2025)

Biodegradable microplastics induce profound changes in lettuce (Lactuca sativa) defense mechanisms and to some extent deteriorate growth traits - Sylwia Adamczyk; Laura J. Zantis; Sam van Loon; Cornelis A.M. van Gestel; Thijs Bosker; Rachel Hurley; Luca Nizzetto; Bartosz Adamczyk; Sannakajsa Velmala (Environmental Pollution, 2024)

Macrofouling remediation strategies for water intakes of desalination and other industrial plants – A review - Ying Shi Chang; Catherine J. Munro; Luca Fortunato; Abdulla AlAli; Christian Marciulescu; Sam Lindsey Harvey; Johannes Vrouwenvelder; Hassan Arafat; Ludovic F. Dumée (Desalination, 2024)

The impact of uninterrupted sitting on central and peripheral cardiovascular function in pre-menopausal and post-menopausal women - Arsalan Moinuddin; Keeron Stone; Louise Turner; Craig Paterson; Nicky Hall; Anne Daykin; Sam Lucas; James Faulkner; Simon Fryer (European Journal of Applied Physiology, 2024)

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Micrometer-resolution X-ray tomographic full-volume reconstruction of an intact post-mortem juvenile rat lung - Elena Borisova; Goran Lovric; Arttu Miettinen; Luca Fardin; Sam Bayat; Anders Larsson; Marco Stampanoni; Johannes C. Schittny; Christian M. Schlepütz (Histochemistry and Cell Biology, 2021)
In this article, we present an X-ray tomographic imaging method that is well suited for pulmonary disease studies in animal models to resolve the full pathway from gas intake to gas exchange. Current state-of-the-art synchrotron-based tomographic phase-contrast imaging methods allow for three-dimensional microscopic imaging data to be acquired non-destructively in scan times of the order of seconds with good soft tissue contrast. However, when studying multi-scale hierarchically structured objects, such as the mammalian lung, the overall sample size typically exceeds the field of view illuminated by the X-rays in a single scan and the necessity for achieving a high spatial resolution conflicts with the need to image the whole sample. Several image stitching and calibration techniques to achieve extended high-resolution fields of view have been reported, but those approaches tend to fail when imaging non-stable samples, thus precluding tomographic measurements of large biological samples, which are prone to degradation and motion during extended scan times. In this work, we demonstrate a full-volume three-dimensional reconstruction of an intact rat lung under immediate post-mortem conditions and at an isotropic voxel size of (2.75 µm) 3 . We present the methodology for collecting multiple local tomographies with 360° extended field of view scans followed by locally non-rigid volumetric stitching. Applied to the lung, it allows to resolve the entire pulmonary structure from the trachea down to the parenchyma in a single dataset. The complete dataset is available online ( https://doi.org/10.16907/7eb141d3-11f1-47a6-9d0e-76f8832ed1b2 ).

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

MDR1 and Cytochrome P450 Gene-Expression Profiles as Markers of Chemosensitivity in Human Chronic Myelogenous Leukemia Cells Treated with Cisplatin and Ru(III) Metallocomplexes - Cesar Augusto Sam Tiago Vilanova-Costa; Hellen Karine Paes Porto; Lucas Carlos Gomes Pereira; Bruno Pereira Carvalho; Wagner Batista dos Santos; Elisângela de Paula Silveira-Lacerda (Biological Trace Element Research, 2015)

Induction of Cell Cycle Arrest and Apoptosis by Ruthenium Complex cis-(Dichloro)tetramineruthenium(III) Chloride in Human Lung Carcinoma Cells A549 - Aliny Pereira de Lima; Flávia de Castro Pereira; Cesar Augusto Sam Tiago Vilanova-Costa; Jordana Ribeiro Soares; Lucas Carlos Gomes Pereira; Hellen Karine Paes Porto; Luiz Alfredo Pavanin; Wagner Batista dos Santos; Elisângela de Paula Silveira-Lacerda (Biological Trace Element Research, 2012)